Pemberdayaan Desa Wisata Berbasis Integrasi Budaya dan Potensi Alam di Desa Tanjung Lanjut Muaro Jambi - Zulgani; Faradina Zevaya; Etik Umiyati; Dwi Hastuti; Rahma Nurjanah (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
Tanjung Lanjut Village has untapped potential in terms of both natural resources and natural beauty that has yet to be fully explored by others. It includes Tangkas Lake, which is a relaxing spot to visit thanks to its cool natural character and unspoiled natural conditions. Unfortunately, community empowerment in Tanjung Lanjut Village in protecting and developing Tangkas Lake's tourism potential has not been fully realized. Through Community Services and the village community's participative approach, it is expected the local community can get the benefit from this program by leveraging the tourism and creative economic sector.